Measuring Spatial Accessibility for Elderly. An Application to Subway Stations in Milan - Manfredini, Fabio; Di Rosa, Carmelo (TeMA - Journal of Land Use, Mobility and Environment, 2018)
This paper presents a method for mapping and measuring accessibility to subway stations for elderly. The methodology measures pedestrian accessibility by means of isochrones to specific urban functions, for quantifying the total amount of elderly people living within each isochrones and for evaluating the presence of services around each station. In particular, a real application on Milan city is carried out with the most updated available data.Main aim is the identification of neighborhoods that present more accessibility problems. The number of inhabitants, and in particular of aged persons living in less accessible areas are therefore quantified, such as the number of activities located within walking distance are counted. The methodology can be applied to different contexts and can be furtherly improved by integrating other information in the model. Accessibility analysis has an increasing role in policy making and evaluation for policies targeted towards social inclusion. because poor pedestrian infrastructures can hinder the potential movement of an increasing amount of urban population.